Investigation of the acetic acid stress response in Saccharomyces cerevisiae with mutated H3 residues - Nitu Saha; Swati Swagatika; Raghuvir Singh Tomar (Microbial Cell)
Enhanced levels of acetic acid reduce the activity of yeast strains employed for industrial fermentation-based applications. Therefore, unraveling the genetic factors underlying the regulation of the tolerance and sensitivity of yeast towards acetic acid is imperative for optimising various industrial processes. In this communication, we have attempted to decipher the acetic acid stress response of the previously reported acetic acid-sensitive histone mutants. Revalidation using spot-test assays and growth curves revealed that five of these mutants, viz., H3K18Q, H3S28A, H3K42Q, H3Q68A, and H3F104A, are most sensitive towards the tested acetic acid concentrations. These mutants demonstrated enhanced acetic acid stress response as evidenced by the increased expression levels of AIF1, reactive oxygen species (ROS) generation, chromatin fragmentation, and aggregated actin cytoskeleton. Additionally, the mutants exhibited active cell wall damage response upon acetic acid treatment, as demonstrated by increased Slt2-phosphorylation and expression of cell wall integrity genes. Interestingly, the mutants demonstrated increased sensitivity to cell wall stress-causing agents. Finally, screening of histone H3 N-terminal tail truncation mutants revealed that the tail truncations exhibit general sensitivity to acetic acid stress. Some of these N-terminal tail truncation mutants viz., H3 [del 1-24], H3 [del 1-28], H3 [del 9-24], and H3 [del 25-36] are also sensitive to cell wall stress agents such as Congo red and caffeine suggesting that their enhanced acetic acid sensitivity may be due to cell wall stress induced by acetic acid.